National Specificity of German Secondary Nominations with Zoonyms Schwein or Sau in Their Composition - Yuriy A. Vorobyev (Publishing house "Sreda", 2024)
The article presents the results of the analysis of German secondary nominations with Schwein or Sau zoonyms. The aim of the analysis was to identify common and nationally specific features of these nominations against the background of their Russian equivalents. The relevance of this study is due to the need for a comprehensive study of secondary nominations, taking into account their axiological aspects, which have a certain cultural uniqueness and cause nationally unique semantic transformations in the lexical meaning of these units. The study used the methods of descriptive, comparative-comparative, component analysis, the method of critical dictionary analysis and dictionary definitions. These methods allowed us to conclude that the nominative potential of the secondary meanings of the German zoonym Schwein or Sau is more pronounced in comparison with their Russian equivalents. The analysis also showed a wider evaluative spectrum of German units and a greater variability of the axiological component in their lexical meaning both under the influence of the contextual environment and without it. Secondary nominations with the indicated zoonyms in their composition were selected as the main material of the study, identified by means of a continuous sampling from German explanatory, encyclopedic, phraseological and linguocultural dictionaries, German language resources, as well as German-Russian dictionaries.